Hasil Keterampilan Membaca Siswa Kelas II Menggunakan Model Tgt Pelajaran Bahasa Indonesia - wahyuni, sri; Pairin M. Basir, Udjang; Yunita Rahma Pratiwi, Emy (IJPSE : Indonesian Journal of Primary Science Education, 2021)
The background of this research is the ability of students' reading skill carried out at Jarak III Elementary School of Wonosalam Jombang, which is less than perfect in learning. It is due to the limited knowledge of teachers in carrying out the learning system by using many kinds of learning models. Meanwhile, the learning model the teachers apply is only the lecturing and assignments model. Besides, its limitations is the lack of the existing media. This research is a qualitative research. It consists of several aspects of treatment and observations aimed at improving the eading skills through the Team Games Tournament (TGT) model for grade II at Jarak III Elementary School of Wonosalam Jombang. This research was conducted at Jarak III Elementary School of Wonosalam Jombang, which involved 17 students consisting of 8 boys and 9 girls who were registered in the 2018/2019 academic year. This study used a descriptive research design. The results showed that the first pre-test got 70.2% of the average results that did not meet the minimum completeness criteria (KKM). After the learning was carried out using the Team Games Tournament (TGT) model, the post test average score of students increased to 85.8%. This average has shown that it meets the minimum completeness criteria (KKM). Thus it can be concluded that learning reading skills with the Team Games Tournament (TGT) model can improve students' reading skills in grade II of Jarak III Elementary School of Wonosalam Jombang.